Exploring the impacts of transfor-sactional leadership on job satisfaction in the context of Malaysian start-up organizations - Mat Ripin, Mardiana (2024)
This study explores the impact of "transfor-sactional" leadership—a blend of transformational and transactional leadership styles—on job satisfaction within Malaysian start-up organizations. The research aims to move beyond the traditional dichotomy of transformational versus transactional leadership by examining how their integration, particularly through the augmentation hypothesis proposed by Bass and Avolio (1993), influences employee satisfaction. The findings reveal that both transformational and transactional leadership qualities significantly enhance job satisfaction among start-up employees. However, the study cautions against an over-reliance on contingent rewards, which, while initially motivating, can diminish intrinsic motivation and harm long-term satisfaction and workplace culture.